PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI LUAS BANGUN DATAR DENGAN MODEL PROBLEM BASED LEARNING DIKELAS IV SDN 01 ULAK KARANG SELATAN - Nurisa Ifadillah; Yetti Ariani; Syafri Ahmad; Salmaini Safitri Syam (STKIP Subang, 2025)
This study aims to describe the improvement of learning outcomes in the material of the Area of Flat Shapes by using the Problem Based Learning (PBL) model in class IV of SDN 01 Ulak Karang Selatan. In this study, the Classroom Action Research (CAR) type was applied using qualitative and quantitative approaches. The subjects in this study were the teacher (researcher) and 22 students consisting of 10 boys and 12 girls. The results of this study showed an increase in: a) the teaching module of cycle I with an average of 83.34% (Good) and cycle II 95.83% (Very Good) b) implementation in the teacher aspect of cycle I with an average of 77.5% (Enough) and cycle II 95% (Very Good), while the implementation in the student aspect of cycle I with an average of 77.5% (Enough) and cycle II 95% (Very Good), c) assessment of students in improving learning outcomes in cycle I obtained 76.09 (Enough) and completeness 52.27% with the success indicator Developing According to Expectations (BSH) and cycle II 83.43 (Good) and completeness 90.91% with the success indicator Developing Very Good (BSB). Based on these results it can be concluded that the Problem Based Learning (PBL) model can improve learning outcomes in the material of the Area of Flat Shapes in grade IV.